Contribution of Leg Muscle Explosive Power and Balance to Sickle Kick Speed in Pencak Silat Athletes - Ahmad, Alvia; Sulfa, Muhammad; Prasetyo, Yudik; Widiyanto; Amiruddin; Muhammad, Fadel (Jurusan Pendidikan Olah Raga dan Kepelatihan FKIP Universitas Jambi, 2026)
The sickle kick is one of the most frequently used techniques in pencak silat competitions and yields high scores, making kick speed a critical performance factor. A faster sickle kick is more difficult for opponents to anticipate, parry, or counter. Several physical components support effective sickle kick performance, including strength, flexibility, power, balance, and agility. This study specifically examined the contribution of leg muscle explosive power and balance to sickle kick speed. This research employed a correlational design involving 30 male athletes from the Pencak Silat Student Activity Unit of Universitas Negeri Yogyakarta (UNY), aged 19–23 years. Data were collected through tests and measurements, using the standing broad jump test to assess leg muscle explosive power, the standing stork test to measure balance, and a 10-second sickle kick speed test to evaluate kick performance. Data analysis was conducted using regression analysis to determine the contribution of each variable. The results revealed that leg muscle explosive power contributed 53.1% to sickle kick speed, while balance contributed 45.7%. When analyzed simultaneously, both variables accounted for 53.6% of the variance in sickle kick speed. These findings highlight the importance of developing leg muscle explosive power and balance within structured training programs to enhance sickle kick speed and overall competitive performance in pencak silat athletes.